(untitled) (Pedagogical Horizons, 2019)
Since the implementation of the educational standards, reading proficiency is one key competence in the European educational policies. The research project “Lesefreunde” Professionals help you read empirically examines a reading workout with more than 700 children over six years. One main purpose of the project is to prove efficacy and long-term effects of additional reading workout conducted by primary school students. In this thesis two central questions occurred: First, is it possible to improve reading skills in terms of reading fluency, reading accuracy, reading speed and reading comprehension within a limited time – frame. Second, in what way does the project make a contribution within the scope of reading didactics, research and school experience? The results of the present study demonstrate an increase of these skills but it is just one part of the project. The second part discusses further possible applications of the higher educational reform.